Engaging Hmong Americans Long-term Use of Healthcare Technology Using Culturally Revised Social Cognitive Theory Model - (:unkn) unknown (My University, 2019)
Purpose: Information technology benefits the world, and it’s required for health care system, such as electronic medical records (EMR). User acceptance model is to systematically study how users come to accept and use a technology. For example, the cultural values of a society restrict use of technology in which an individual can be less incline to accept it. There is a significant amount of Hmong population in great Milwaukee area. Spirits are a central part of Hmong religious beliefs where the spirit is tied to health. Chronic disease is believed to be caused by bad actions done by the individual’s past lives according to traditional beliefs and as a result may influence families’ willingness to accept a prescribed treatment. The social cognitive theory (SCT) model assists in attaining information by measuring user acceptance through three criteria: behavior, personal, and environment. In this study, we will culturally revised SCT model to engage Hmong Americans long-term use of healthcare technology. Our mainly research methodologies are literature review and modeling. The obtained results can be used for information technology applications in healthcare for Hmong Americans and assist in increasing user acceptance in the Hmong community. Method: Create a user acceptance model(s) to gauge community’s engagement level health related technology. Review through several user acceptance models that serve as potential model to involve key factors that are unique to the target group. Choose one model that can be revised to fit the Hmong community as well as possible. Gathering of related literature served as a foundation in understanding the community’s culture and cultural factors were drawn from them to revise the SCT model. Results: Incorporating Hmong cultural factors into a chosen user acceptance model gave an overview of various determinants that can help with understanding what things can influence a Hmong American’s behavior and attitude towards health. There are no rules that would restrict them from using health technology and utilize either or both traditional and western method for health management. Hmong Americans rely on health providers for health information particularly for those who have trouble finding other sources of information, making successfully building a rapport between the two all the more important. Discussion: It can be difficult to ascertain as to how well this group perceive health technology when there is little research done about their usage of any kind of health technology. Understanding how they view health can allow planning to devise ways to appeal to that view to increase usage. Future research directions can utilize a user acceptance model for other lesser known ethnic groups.